Pengembangan tes diagnostik berbasis web pada materi larutan elektrolit dan nonelektrolit - Hidayah, Putri; Muchtar, Zainuddin (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to analyze (1) the feasibility of web-based diagnostic tests on electrolyte and nonelectrolyte solution materials, (2) student concept understanding profiles after using web-based diagnostic tests on electrolyte and nonelectrolyte solution materials, (3) chemistry teacher responses to web-based diagnostic tests on electrolyte and nonelectrolyte solution materials, (4) student responses to web-based diagnostic tests on electrolyte and nonelectrolyte solution materials. The method used in this development research is the ADDIE method which consists of 5 stages of treatment, namely analysis, design, development, implementation and evaluation. The results showed that the web-based diagnostic test developed was considered very feasible and effective, with positive responses from teachers and students regarding presentation, language, content, and benefits. This test also succeeded in improving students' concept understanding on electrolyte and non-electrolyte solution materials, so it has the potential to be used as a learning evaluation tool.